Biology of Bemisia tabaci (Genn.) biotype B (Hemiptera: Aleyrodidae) in tomato genotypes in two seasons - Toscano, Luciana Claudia; Boica Junior, Arlindo Leal [UNESP]; Mamore Martins, Gustavo Luis; Maruyama, Wilson Itamar (Univ Estadual Mato Grosso Sul, 2016)
Bemisia tabaci biotype B is currently one of the most important pests of tomato crop. This work aimed to study the pest biology in tomato genotypes in two seasons. The test was conducted in a greenhouse in the experimental area of the Plant Protection Department of the FCAV/UNESP, Jaboticabal, SP, Brazil. Two commercial genotypes (hybrid Bruna VFN and Santa Clara) and four exotic genotypes (LA 716, PI 134417, PI 127826 and PI 127827) were used in two different seasons, winter and spring. The incubation period ranged from 12.11 days (PI 134417) to 13.85 days (LA 716). The nymphal period ranged from 21.12 days (PI 127827) to 22.56 days (hybrid Bruna VFN). Total development period ranged from 37.31 days (hybrid Bruna VFN) to 34.48 days (PI 127827). Adult longevity was higher for insects from the exotic genotype PI 127826 (1.5 days), which differed significantly from the other genotypes, which showed longevity ranging from 1.00 to 1.10 days. The total period of development was 35.92 at the time winter and 15.89 days in season spring. Thus, the insect cycle was 2.26 times greater at the winter in relation to the spring, demonstrating the latter being more suitable for the development of the pest.
Keywords: Lycopersicon; white fly; plants resistance